Overview of Public Knowledge About the Use of Rational Anti-Biotic in Liwuto Village, Makassar Island, Baubau City - Narti Badarudin; Suparman Supardi; Yuyun Wirasasmita (Journal of Health Science and Pharmacy, 2026)
Background: Antibiotics are medications used to eliminate or inhibit the growth of microorganisms that cause infections. However, the irrational use of antibiotics has become a major public health concern due to its contribution to antibiotic resistance. Antibiotic resistance occurs when bacteria are no longer susceptible to the effects of antibiotics, making infections more difficult to treat. Factors contributing to antibiotic resistance include inappropriate antibiotic use, incorrect treatment regimens, adverse drug effects, and limited public knowledge regarding proper antibiotic use. Therefore, assessing community knowledge about antibiotics is essential to support rational antibiotic use and prevent the development of resistance. Objective: This study aimed to assess the level of knowledge regarding the rational use of antibiotics among residents of Liwuto Village, Makassar Island, Baubau City. Methods: A descriptive cross-sectional study was conducted using a questionnaire-based survey. Primary data were collected directly from 100 respondents residing in Liwuto Village, Makassar Island, Baubau City. The data were analyzed descriptively to determine the level of community knowledge regarding the rational use of antibiotics. Results: The findings revealed that the majority of respondents had inadequate knowledge regarding the rational use of antibiotics. Of the 100 respondents, 74% were categorized as having poor knowledge, 18% had moderate knowledge, and only 8% demonstrated good knowledge. These results indicate that awareness and understanding of appropriate antibiotic use remain low among the community. Conclusion: The level of knowledge regarding the rational use of antibiotics among residents of Liwuto Village, Makassar Island, Baubau City, was generally low. The high proportion of respondents with poor knowledge highlights the need for educational interventions and public health campaigns to improve awareness of appropriate antibiotic use and to reduce the risk of antibiotic resistance. Keywords: Antibiotics; Rational Use of Antibiotics; Antibiotic Resistance; Knowledge; Community Awareness.